Fibrosis biomarkers as predictors of left atrial appendage thrombosis in patients with nonvalvular atrial fibrillation - T. P. Gizatulina; N. Yu. Khorkova; A. V. Mamarina; A. V. Belokurova; L. U. Martyanova; T. I. Petelina (Российский кардиологический журнал)
Aim. To compare clinical, echocardiographic characteristics and blood biomarkers in patients with nonvalvular atrial fibrillation (AF) depending on the presence of left atrial appendage (LAA) thrombus and to identify independent predictors of LAA thrombosis.Material and methods. Patients with nonvalvular AF subjected to transesopha geal echocardiography before catheter ablation were divided into 2 groups comparable by sex and age: group 1 (n=45) — with LAA throm bosis; group 2 (n=97) — without LAA thrombosis. The patients underwent transthoracic and transesophageal echocardiography. In addition, the following blood biomarkers were analyzed: NT-proBNP (pg/ml), GDF-15 (pg/ml), TGF-β1 (pg/ml), PIIINP (ng/ml), high-sensitivity C-reactive protein (hsCRP) (mg/l), cystatin C (mg/l).Results. In group 1, persistent AF, coronary artery disease, heart failure were more often noted. In addition, group 1 patients had higher volume indices of both atria, left ventricular mass index and pulmonary artery systolic pressure, as well as lower left ventricular ejection fraction and blood flow velocity in the LAA. There were no differences in the groups in terms of the mean CHA2DS2VASc score, the proportion of patients taking oral anticoagulants (OAC), and the OAC spectrum. In group 1, higher levels of NT-proBNP (p=0,0001), GDF15 (p=0,0001), PIIINP (p=0,0002) were found with no differences in the levels of TGF-β1, hsCRP and cystatin C. A stepwise logistic regression revealed independent predictors of LAA thrombosis: LA volume index (ml/m2) — odds ratio (OR)=1,084, 95% confidence interval (CI) 1,028-1,143 (p=0,003); GDF15 ≥933 pg/ml — OR=3,054, 95% CI, 1,260-7,403 (p=0,013); PIIINP ≥68 pg/ml — OR=5,865, 95% CI, 2,404-14,308 (p<0,001). There were following model quality parameters: AUC=0,815 (p<0,001), specificity, 74,4%, sensitivity, 72,7%.Conclusion. In patients with nonvalvular atrial fibrillation taking OAC, serum levels of fibrosis biomarkers PIIINP ≥68 pg/mL and GDF-15 ≥933 pg/mL, along with the left atrial volume index, were independent predictors of LAA thrombosis.